Recent Advance in Tunable Single-Frequency Fiber Laser Based on Two-Dimensional Materials - 哲, 魏; Wei, Zhe; Chen, Shuangcheng; Ding, Jianyi; Sun, Bo; Qi, Xinyuan; Lu, Baole; Bai, JinTao (Frontiers in Physics, 2021)
Two-dimensional (2D) materials possess optoelectronic and nonlinear optical properties make them used in many fields such as optical modulator, optical switch, and single frequency (SF) fiber lasers as a saturable absorber (SA) in the laser cavity. This review deals with recent advances in wavelength tunable single frequency fiber laser based on these properties. It extends the contents from previous reviews on pulsed fiber lasers to SF fiber lasers which have emerged in recent years. First, the research status of 2D materials, including the structural characteristics and properties of some typical cases and their saturable absorption characteristics are introduced. After that, the principle and some applicable technologies with these 2D materials to achieve the wavelength tunable SF operation are discussed. Further, the latest research progress on such fiber lasers are summarized. Finally, a discussion on future prospects and challenges are included.